Risk stratification and management algorithms for patients with diffuse large B-cell lymphoma and CNS involvement - Calimeri, Teresa; Lopedote, Paolo; Ferreri, Andrés J. M. (Annals of Lymphoma, 2019)
Central nervous system involvement is a hallmark of worse prognosis in all types of cancer, including diffuse large B-cell lymphoma. Secondary central nervous system lymphoma diagnosed both at first presentation and at relapse in diffuse large B-cell lymphoma patients represents an important unmeet clinical need. It is a rare, early, fatal, and preventable condition. Central nervous system dissemination occurs in 5% of all diffuse large B-cell lymphoma, usually during primary therapy or the first year of follow-up, and most of affected patients die of lymphoma in everyday practice, with a 4-year overall survival close to 40% in prospective trials. A diffuse use of an efficient prophylaxis to prevent this complication could reduce overall mortality in diffuse large B-cell lymphoma. However, prophylaxis strategies are associated with some forms of toxicity, which is severe in some subjects. Accordingly, this option should be used only in some subgroups of patients with “high risk” of developing central nervous system involvement. Unfortunately, variables and scores proposed to identify “high risk” patients show a low diagnostic sensitivity, resulting in an overtreatment for a high proportion of patients. Moreover, there is still no consensus on the most effective prophylaxis modality to prevent central nervous system dissemination as well as on the standard of care that can be used in patients with secondary central nervous system lymphoma. A few prospective trials focused on new approaches to secondary central nervous system lymphoma patients have been published. Overall, these studies suggest that combinations of drugs with good central nervous system penetrance and anti-lymphoma efficacy are associated with improved outcome, in particular in patients managed with autologous stem cell transplantation. In this review, we discuss the current open questions in the field, propose risk stratification and management algorithms and analyze evidence supporting therapeutic choices in secondary central nervous system lymphoma patients.